2016
DOI: 10.1016/j.ypmed.2016.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Active school transport and fast food intake: Are there racial and ethnic differences?

Abstract: Objectives To investigate whether active school transport was associated with fast food consumption, and to examine differences across racial/ethnic groups. Methods Adolescent data (n=3,194) from the 2009 California Health Interview Survey were analyzed with logistic regression models to examine the association between active school transport (AST) and fast food intake across racial/ethnic groups. Results In the overall sample, AST during 1–2 days in the past week was associated with greater likelihood of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Active school travel may also increase the exposure of children to fast-food purchasing opportunities, differentially by ethnicity. In a US study, active school travel increased the exposure of Latino children in California to fast-food but had limited impact for other ethnicities [ 52 ]. In the current study, children of all ethnicities were exposed to a higher density of unhealthy food outlets compared to healthy food outlets.…”
Section: Discussionmentioning
confidence: 99%
“…Active school travel may also increase the exposure of children to fast-food purchasing opportunities, differentially by ethnicity. In a US study, active school travel increased the exposure of Latino children in California to fast-food but had limited impact for other ethnicities [ 52 ]. In the current study, children of all ethnicities were exposed to a higher density of unhealthy food outlets compared to healthy food outlets.…”
Section: Discussionmentioning
confidence: 99%
“…Australian children are exposed to high levels of outdoor advertising for unhealthy food and drink on school routes, 32 with exposure to unhealthy food advertising known to encourage a preference for and purchasing of unhealthy foods by children 33 . International studies have found that among adolescents, active travel is associated with an increased likelihood of consumption of fast food compared to car travel, related to higher fast‐food purchasing opportunities 34 , 35 . Secondary students with pocket money are more likely to consume fast food (overall) than those with no pocket money 36 .…”
Section: Discussionmentioning
confidence: 99%
“…33 International studies have found that among adolescents, active travel is associated with an increased likelihood of consumption of fast food compared to car travel, related to higher fast-food purchasing opportunities. 34,35 Secondary students with pocket money are more likely to consume fast food (overall) than those with no pocket money. 36 Interventions to increase active travel should also mitigate the potential unintended consequences related to increased exposure to unhealthy food marketing and environments along the school journey.…”
Section: Discussionmentioning
confidence: 99%